Migrants and citizens : demographic change in the European state system - Koslowski, Rey (Book collections on Project MUSE., 2000)
The Berlin Wall falls as thousands of East Germans move to the West; after the Iron Curtain lifts, West Europeans brace for mass migrations from Eastern Europe; millions of refugees flee Iraq, Bosnia, Haiti, Rwanda, and other strife-torn nations. The ...